Primary amines from lignocellulose by direct amination of alcohol intermediates, catalyzed by RANEY® Ni. Issue 19 (23rd August 2022) - Wu, Xianyuan; De Bruyn, Mario; Barta, Katalin
Abstract : A highly efficient RANEY® Ni-based amination methodology using ammonia that is capable of converting lignocellulose-derived alcohol intermediates into their corresponding primary amines in high selectivity, following hydrogen borrowing methodology. Abstract : Primary amines are crucially important building blocks for the synthesis of a wide range of industrially relevant products. Our comprehensive catalytic strategy presented here allows diverse primary amines from lignocellulosic biomass to be sourced in a straightforward manner and with minimal purification effort. The core of the methodology is the efficient RANEY® Ni-catalyzed hydrogen-borrowing amination (with ammonia) of the alcohol intermediates, namely alkyl-phenol derivatives as well as aliphatic alcohols, obtained through the two-stage LignoFlex process . Hereby the first stage entails the copper-doped porous metal oxide (Cu20PMO) catalyzed reductive catalytic fractionation (RCF ) of pine lignocellulose into a crude bio-oil, rich in dihydroconiferyl alcohol (1G ), which could be converted into dihydroconiferyl amine (1G amine ) in high selectivity using ammonia gas, by applying our selective amination protocol. Notably also, the crude RCF -oil directly afforded 1G amine in a high 4.6 wt% isolated yield (based on lignin content). Finally it was also shown that the here developed Ni-catalysed heterogeneous catalytic procedure was equally capable of transforming a range of aliphatic linear/cyclic primary/secondary alcohols – available from the second stage of the LignoFlex procedure – into their respective primary amines.